The Origin and Onset of Thrombus Disease Collapsed Balancing Function of Immune Cells and Triggering Factors - Wang, Lemin (Springer Singapore, 2018)
This book analyzes the internal and external causes of acquired and familiar venous thrombosis and proposes the origins and onset of venous thrombus diseases and their triggering factors. It discusses venous and arterial thrombus in two parts, each starting from the genomics and the findings of immunocytological research conducted in a variety of clinical groups and on different experimental models and revealing the mechanisms behind the development of thrombotic diseases and the pathogenesis processes. Further, the book describes the clinical manifestation and the nature of the diseases. The book offers valuable insights important in the prevention and treatment of thrombotic disease.